Functional role of a polymorphism in the Pannexin1 gene in collageninduced platelet aggregation - Molica, Filippo; Monyer, Hannah (Thrombosis and haemostasis, 2017)
Pannexin1 (Panx1) forms ATP channels that play a critical role in the immune response by reinforcing purinergic signal amplification in the immune synapse. Platelets express Panx1 and given the importance of ATP release in platelets, we investigated Panx1 function in platelet aggregation and the potential impact of genetic polymorphisms on Panx1 channels. We show here that Panx1 forms ATP release channels in human platelets and that inhibiting Panx1 channel function with probenecid, mefloquine or specific 10Panx1 peptides reduces collagen-induced platelet aggregation but not the response induced by arachidonic acid or ADP. These results were confirmed using Panx1-/- platelets. Natural variations have been described in the human Panx1 gene, which are predicted to induce non-conservative amino acid substitutions in its coding sequence. Healthy subjects homozygous for Panx1-400C, display enhanced platelet reactivity in response to collagen compared with those bearing the Panx1-400A allele. Conversely, the frequency of Panx1-400C homozygotes was increased among cardiovascular patients with hyper-reactive platelets compared with patients with hypo-reactive platelets. Exogenous expression of polymorphic Panx1 channels in a Panx-deficient cell line revealed increased basal and stimulated ATP release from cells transfected with Panx1-400C channels compared with Panx1-400A expressing transfectants. In conclusion, we demonstrate a specific role for Panx1 channels in the signalling pathway leading to collagen-induced platelet aggregation. Our study further identifies for the first time an association between a Panx1-400A>C genetic polymorphism and collagen-induced platelet reactivity. The Panx1-400C variant encodes for a gain-of-function channel that may adversely affect atherothrombosis by specifically enhancing collagen-induced ATP release and platelet aggregation.
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 12.06.2020